Strategic Learning and Metacognitive Skills in Mathematics of The Bachelor of Industrial Technology at A University in Roxas City, Capiz - Icamina, Princess May A. (Future Science / FSH-PH Publications, 2023)
Students frequently believe that mathematics is a challenging subject to learn. The learners must have the necessary skills to study the material quickly as a result. The idea that learners can select various methods for completing particular tasks is implied frequently by the term